Coefficients Of The Inverse Of Strongly Starlike Functions. - M. Ali, Roslhan (Persatuan Sains Matematik Malaysia, 2003)
For the class of strongly starlike functions, sharp bounds on the first four coefficients of the inverse functions are determined. A sharp estimate for the Fekete-Szego coefficient functional is also obtained. These results were deduced from non-linear coefficient estimates of functions with positive real part.